Childbirth-related posttraumatic stress symptoms: exploring the predictive potential of intrapartum hotspots - Meike K. Blecker; Daria Daehn; Sinha Engel; Susann Steudte-Schmiedgen; Susan Garthus-Niegel; Christine Knaevelsrud; Sarah Schumacher (Journal of Psychosomatic Obstetrics and Gynecology)
Childbirth-related posttraumatic stress symptoms (CB-PTSS) affect around 12% of postpartum individuals. While the subjective experience of childbirth is a key predictor of CB-PTSS, the specific defining characteristics of negative birth experiences remain poorly understood. This study aims to refine our understanding of negative birth experiences by investigating intrapartum hotspots, i.e. moments of extreme distress, and their association with CB-PTSS. In a cross-sectional study of N = 1,140 individuals who had given birth eight to ten weeks before, we examined the following: the types of hotspots, differences in hotspot-related distress, interpersonal difficulties during the hotspot, and CB-PTSS between the various types of hotspots and whether hotspot-related distress and interpersonal difficulties independently predicted CB-PTSS. Participants completed several items based on previous qualitative work [1] to assess the worst hotspot, hotspot-related distress, and interpersonal difficulties during the hotspot and the City Birth Trauma Scale to measure CB-PTSS, alongside relevant pregnancy- and birth-related questions. Medical interventions were the most frequently experienced worst hotspot and separation from the child was associated with the highest levels of hotspot-related distress, interpersonal difficulties, and CB-PTSS. Hotspot-related distress and interpersonal difficulties independently predicted CB-PTSS. Examining intrapartum hotspots poses a promising approach to define highly negative birth experiences.